Binocular Diplopia as Ocular Manifestation in Pediatric Miller Fisher - Zhafira, Dinda; Prastyani, Reni; Gunawan, Prastiya Indra; Noviandi, Riza; Sunny Mariana Samosir (South Eastern European Journal of Public Health, 2024)
Miller Fisher Syndrome (MFS) is a rare variant of neuropathy spectrum of Guillain-Barré syndrome that occur less frequently in children. 11 years old suffered from weakness of limbs with walking and posture bearing difficulty for 3 days before admission. Patient also had complaint of double vision with gaze restriction and difficulty while chewing or swallowing. During admission patient had respiratory failure that inquired intubation and ventilator support. Clinical improvement was achieved after patient was intravenous immunoglobulin (IVIG) for 5 days. First ophthalmology examination showed 15 degrees exotropia of left eye with 30 prism dioptres (PD) at near and far distance. The Worth four dot test revealed crossed diplopia, along with gaze restrictions in all directions. Follow-up 2 months after admission, the patient's symptoms had resolved. Miller Fisher Syndrome (MFS) is diagnosed clinically, characterized by the triad of ataxia, areflexia, and ophthalmoplegia. Treatment for MFS primarily involves supportive care, including respiratory support and immunotherapy if required. The prognosis for MFS is generally favorable. Recovery usually starts in two until four weeks after onset and generally completing within six months.